The Concept Of Physical Education and Its Integration With Mental Health According to The Qur'An and Hadith - Eliwatis, Eliwatis; Rusydi, Rusydi; Charles, Charles; Maimori, Romi; Herawati, Susi (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2022)
Physical education in the view of Islam cannot be underestimated, because between the physical and the spiritual man is a unity. When physical education is carried out, it actually includes education for the human spirit, and vice versa. A popular motto is